Dark tourism in Serbia: Case study of the Kragujevački oktobar Memorial Park - Miletić, Radovan; Pantović, Danijela; Veliverronena, Linda (Hotel and Tourism Management, 2023)
The study presented in the paper employs the benefit-based approach to analyse the potentials of dark tourism as a context which outlines cultural tourism within a broader framework of contemporary tourism development. The focus of the research is the Kragujevački oktobar Memorial Park, which is one of the most infamous dark tourism spots in Serbia – well known among its residents as well as the Balkan region. The research looks into the travellers’ reasons for visiting the sight, their on-site experiences and benefits gained. The results of the study highlight the identified motivation and reasons for visiting the Memorial Park, as well as provide a comprehensive overview of the ways the visitors are affected.